ANALISIS KADAR ENZIM CHOLINESTERASE PADA PETANI YANG MENGGUNAKAN PESTISIDA DI DESA LOA JANAN ULU - Niken Syafitri (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
In Indonesia, many farmers use pesticides, especially in East Kalimantan, specifically in Loa Janan Ulu Village. Farmers use pesticides as an effort to reduce pest or insect attacks. The use of pesticides poses a risk to humans in the form of acute chronic poisoning and even death. Cholinesterase is an enzyme found in cell fluids whose job is to stop the action of acetylcholine by hydrolyzing it into choline and acetic acid. The aim of this research was to determine the levels of the cholinesterase enzyme in farmers who use pesticides in Loa Janan Ulu village. The type of research used was descriptive with a sample of 80 farmers in Loa Janan Ulu village who met the inclusion and exclusion criteria. The sampling technique was carried out using purposive sampling, with univariate analysis. The research results are based on the characteristics of respondents in the largest age group, namely 51-60 years (15 respondents), working period 21-30 years (14 respondents). The frequency of spraying was once a week (25 respondents). It can be concluded that in 33 samples the cholinesterase enzyme levels of 95% of farmers met normal standards and 5% did not meet normal standards.